The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c6dt04535a
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-1D chains of dinickel lantern complexes and their magnetic properties

Abstract: Four new quasi-1D Ni-lantern chain complexes of the form [Ni(SOCR)(L)] (R = Ph, L = DABCO (1); R = Ph, L = pyz (2); R = CH, L = DABCO (3); R = CH, L = pyz (4)) were prepared from the reaction of [Ni(SOCR)(EtOH)], R = CH or Ph, with the N,N'-donor bridging ligands pyrazine (pyz) or 1,4-diazabicyclo[2.2.2]octane (DABCO). Reaction of [Ni(tba)(EtOH)], (tba = thiobenzoate) with the mono-N donor ligand quinuclidine (quin) gave the discrete Ni-lantern complex [Ni(tba)(quin)] (5), whereas reaction with pyridine led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 94 publications
2
18
2
Order By: Relevance
“…In the present structural model, the transition metal in each lantern unit has a different coordination environment (see Figure 1), which leads to d-oribital energy levels of Ni(II) ions in two lantern units split in different manners, as shown in Figure 3. The [NiO 4 ] and [NiS 4 ] planes of the structures A and B are twisted about the Ni−Ni axis by 15.76°and 12.77°, respectively, which is slightly smaller than the experimental values reported by Doerrer et al 37 However, the Ni−Ni distances in optimized structure A were 0.770 and 0.764 Å larger than that in the experimental products ([Ni 2 (tba) 4 (EtOH)] and [Ni 2 (SAc) 4 (EtOH)]). 37 These difference can be ascribed to two reasons: One is a slight steric effect between coordinated Ni planes arising from the absence of substituted groups in thioformic acid backbone ligands.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…In the present structural model, the transition metal in each lantern unit has a different coordination environment (see Figure 1), which leads to d-oribital energy levels of Ni(II) ions in two lantern units split in different manners, as shown in Figure 3. The [NiO 4 ] and [NiS 4 ] planes of the structures A and B are twisted about the Ni−Ni axis by 15.76°and 12.77°, respectively, which is slightly smaller than the experimental values reported by Doerrer et al 37 However, the Ni−Ni distances in optimized structure A were 0.770 and 0.764 Å larger than that in the experimental products ([Ni 2 (tba) 4 (EtOH)] and [Ni 2 (SAc) 4 (EtOH)]). 37 These difference can be ascribed to two reasons: One is a slight steric effect between coordinated Ni planes arising from the absence of substituted groups in thioformic acid backbone ligands.…”
contrasting
confidence: 62%
“…The [NiO 4 ] and [NiS 4 ] planes of the structures A and B are twisted about the Ni−Ni axis by 15.76°and 12.77°, respectively, which is slightly smaller than the experimental values reported by Doerrer et al 37 However, the Ni−Ni distances in optimized structure A were 0.770 and 0.764 Å larger than that in the experimental products ([Ni 2 (tba) 4 (EtOH)] and [Ni 2 (SAc) 4 (EtOH)]). 37 These difference can be ascribed to two reasons: One is a slight steric effect between coordinated Ni planes arising from the absence of substituted groups in thioformic acid backbone ligands. On the other hand, axial ligands in our model and experimental complexes have different coordination bonding characters.…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…[6-9, 11, 12] Theb inding of an axial ligand changes the coordination sphere at the metal site to square-pyramidal thus rendering such PW complexes paramagnetic.Asearch in the Cambridge Structural Database revealed that in O,O-, S,O-and S,S-bridged Ni 2 -PWs,the {NiO 4 }s ites are always coordinated by an axial ligand, while the {NiS 4 }a re not. [14] S,N-Bridged Ni 2 -PWs have been reported either with [11] or without [12,15] axially bound donor ligands.T ot he best of our knowledge,i nn one of those both situations have been realized within ag iven paddlewheel. However,t his would be highly interesting as it offers the possibility for molecular,m agnetic switching triggered by [*] Dr.K .M.F ürpaß, Dr.L.M.P eschel, Prof. Dr. 2021 The Authors.…”
Section: Introductionmentioning
confidence: 99%
“…[6-9, 11, 12] Theb inding of an axial ligand changes the coordination sphere at the metal site to square-pyramidal thus rendering such PW complexes paramagnetic.Asearch in the Cambridge Structural Database revealed that in O,O-, S,O-and S,S-bridged Ni 2 -PWs,the {NiO 4 }s ites are always coordinated by an axial ligand, while the {NiS 4 }a re not. [14] S,N-Bridged Ni 2 -PWs have been reported either with [11] or without [12,15] axially bound donor ligands.T ot he best of our knowledge,i nn one of those both situations have been realized within ag iven paddlewheel. However,t his would be highly interesting as it offers the possibility for molecular,m agnetic switching triggered by ad onor ligand.…”
Section: Introductionmentioning
confidence: 99%